Analysis of the Role of the Airport Rescue and Fire Fighting Unit (ARFF) for Airside Safety at Adi Soemarmo Solo Airport - Joshua Victory Cendikia Putra; Rahimuddin Rahimuddin (CV. Rayyan Dwi Bharata, 2023)
A role is something that emphasizes the duties and obligations of a person and as a process of achievement, it means that someone has carried out a role. The role of the ARFF Unit is important in monitoring security and safety on the air side and overseeing the movement of aircraft, vehicles, passengers and goods in the airside area as well as handling or monitoring runways or runways. The ARFF unit at Adi Soemarmo Solo Airport needs a limited number of personnel, because the unit lacks finances due to the Covid-19 period and officials who have aged or retired. The purpose of this research study was to determine the Role Analysis of the Airport Rescue And Fire Fighting Unit (ARFF) for Airside safety and the Readiness of the ARFF Unit when dealing with accidents and incidents at Adi Soemarmo Solo Airport. Research using qualitative research methods, namely data using primary and secondary data. Primary data were obtained from interviews, observations and field documentation regarding airside safety at airports. Secondary Data is data obtained from photographs, documents and others in the company unit. The results of the research, from the main and principal roles or tasks that have become the obligations of the ARFF Unit must be demanded according to the Stipulation Letter in the KP regulations. Number 14 of 2015 regarding Facilities, Human Resources and Standard Operating Procedures. The role of the Airport Rescue And Fire Fighting Unit (ARFF) at Adi Soemarmo Airport is now not in accordance with the rules with the reality on the ground, so there is a difference from according to the applicable provisions and in the field what occurs is not following according to procedures, especially at Adi Soemarmo Solo Airport. If the financial condition has improved one day it will make it easier for the tasks and obligations to fulfill them and overcome if there are accidents and incidents regarding airside safety at Adi Soemarmo Solo Airport.